PENDIDIKAN AGAMA BAGI ANAK PEREMPUAN DI DESA MURUNG BINJAI KECAMATAN LAMPIHONG KABUPATEN BALANGAN - Marni Marni; Abdul Wahab Syakhrani (CV. ADIBA AISHA AMIRA, 2025)
This study is motivated by the public's view regarding religious education for girls, where girls still do not receive enough religious education from their parents, but only limited to lessons in public schools where religious lessons are very minimal in terms of time. The purpose of this study was to determine parents' perceptions regarding the opportunity to get religious education for girls and the religious education material taught by parents to girls. The method used is a qualitative method, the subjects of this study were parents who have children with different genders totaling 5 families. While the object of the study was the possibility of gender inequality in education in Murung Binjai, Kusambi Hulu Village. Data collection techniques include observation, interviews and documentation. Data were created using data reduction techniques, data display and data verification. Data were analyzed using qualitative descriptive methods. The results of the study can be concluded that parents who have children with female gender have provided religious education for their daughters well, according to the abilities of the parents to their daughters, the religious education material taught by parents to their daughters includes an invitation to carry out the obligation of praying 5 times a day and getting used to reciting the quran every day and the perception of parents towards religious education for daughters shows the results that parents are aware of the importance of religious education for their daughters so that they try to educate based on religious guidance and send their children to schools that have religious lessons, and the above shows that the initial assumption of this study does not apply